Treating the mind (akal budi) from the perspective of Syair Ikan: manuscript form Leiden Netherland - Awang Pawi, Awang Azman; Nik Muhamad Affendi, Nik Rafidah; Md Zain, Rosnani; Hamdan, Rahimah; Roslan, Nur Maisarah (ASR Research India, 2022)
The Malay communities themselves often considered the traditional literature including syair as nothing more than an expression of feeling and lovely phrasing. This statement showed that the Malay community looked literary tradition as not involving ‘the treatment of mind’(akal budi). In the context of this study, ‘the treatment of mind’ carried the meaning of maintaining a healthy mind. Therefore, this study classified and analyzed the mind treatment using an old Malay manuscript of Syair Ikan which was stored in the Library of Leiden, Netherlands. The Budi Theory and the Poetic of Malay Literature Theory would be used in the study. The findings of the study showed that there were three dominant ways to treat the mind in Syair Ikan, namely religion, family and symbols of animals. These three dominant ways are used to convey messages, reprimands and as advice to the society.